Formulation body scrub from silica gel of palm oil shell (Elaeis Guineensis Jacq.) - Ruri Putri Mariska; Yulianis Yulianis; Anggun Suntari (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background: Oil palm shell is a waste of oil palm plants that can be used as a source of silica gel because it contains SiO2. This study aims to determine the oil palm shell silica gel can be used as an active ingredient in the manufacture of body scrubs. Method: This study uses active ingredients with various concentrations of 2,5%, 5%, and 10%. The process of making silica gel starts with ashing, washing, making a sodium silicate solution, and adding NaOH. The preparation test includes an organoleptic test, homogeneity test, pH test, dispersibility test, adhesion test, irritation test, dead skin cell removal test, and stability test. Results: From the results of this study, the SiO2 content of palm oil shell silica gel is as much as 43% with XRF testing, and XRD results at an angle of 2Ï´=22,93Âº. The FTIR results showed the presence of a Si-OH group at a wave number of 3439.08 cm -1, a Si-O-Si group at a wave number of 1020,34 cm -1, and a -OH group at a wave number of 806,25 cm -1. The preparations that have been made meet the physical evaluation of the preparations, namely in the form of semi-solid, white color, and smells of oleum citri. Each homogeneous preparation, pH with a value ranging from 4,7 to 6,5, does not irritate the skin, meets the requirements of the spreadability test and adhesion test, has poor stability because the pH value has increased and decreased, has a good keratin content value, and the stability test of the formula against temperature at pH showed significant results (p>0.05). Conclusion: This research concludes that palm oil shell silica gel can be formulated as an active ingredient in making body scrubs and has the effect of removing dead skin cells on the skin.